Literature Review of Women Experience in Prison - Nur Oktavia Hidayati; Frans Raimond Tonjau; Mela Yulianti; Silvi Riana Putri; Wiani Syawalia Fitri (CV. Multi Kreasi Media, 2025)
Women who are imprisoned are believed to have a higher vulnerability to experiencing mental disorders compared to male prisoners even though the rights and obligations of both are the same. Female prisoners have higher psychiatric morbidity than male prisoners, experiencing psychosis, emotional disturbances, and anxiety disorders. If we only focus on stressful events, then we cannot fully explain their experiences while in prison. The response to stress for each individual is different, and the way each individual deals with stress is also different. The purpose of this study is to find out what experiences happen to women who are imprisoned. The method used is literature review. A systematic search of the literature in the 2012-2022 range was conducted using the PubMed, Scopus EBSCO, and Google Scholar databases. Search keywords for the article include “Experience”, Female or Woman”, and “Inmate, or Offenders, or Prisoners, or Convicts, or Incarcerated Individuals